A Vision Training Program's Impact on Ice Hockey Performance. - Jenerou, Alison; Morgan, Bruce; Buckingham, Robert S. (Optometry & Visual Performance, 2015)
Background: This study was carried out to determine whether a preseason vision training program would improve visual skills and season success in a Division I men's ice hockey team. Methods: A six-week vision training program was implemented with the Ferris State University Men's Ice Hockey team during their pre-season workouts. Vision training incorporated binocular and accommodative training along with dynamic visual skills training. Results: The study showed an improvement in base out vergence ranges, binocular accommodative facility, and Wayne Saccadic Fixator (WSF) scores and was viewed by players to have made a positive impact on their individual performance. The pre- and postvision training goals, shots on goal, and shooting percentage all significantly improved following training. Conclusion: The vision training program during preseason workouts had a positive impact on the players' visual skills important for hockey. The players' perception of their vision and how they were using their vision during competitive play also showed a significant change. The majority of the players felt that vision training was an effective use of their practice time allotted by the NCAA.